Perlindungan Data Pribadi dan Kaitannnya dengan Asas Publisitas pada Sertifikat Tanah Elektronik (RechtJiva, 2025)
The conflict between the principle of publicity in Article 4 paragraph (2) of PP No. 24 of 1997 requires openness of information related to physical and legal land data to guarantee legal certainty and transparency with the principle of confidentiality in Article 3 letter h of Law No. 27 of 2022 emphasizing the importance of protecting data from unauthorized access. This study explores the disharmony between protecting personal data and ensuring public access to information in electronic land certificates. While the principle of openness ensures public access to physical data and legal data for legal certainty, electronic land certificates present challenges in protecting personal data, leading to a conflict between these principles. This thesis uses a normative juridical method, focusing on doctrinal analysis of theories, concepts, and legislation. The study uses statutory and conceptual approaches, analyzing primary, secondary, and tertiary legal materials through grammatical and systematic interpretation. The results of this research are that there is a norm conflict between the principles of publicity and confidentiality in the context of electronic land certificates. This disharmony creates legal uncertainty and poses risks to individual privacy rights. To resolve this conflict, the principle of lex superiori derogate legi inferiori should be adopted, with the PDP Law as the primary reference. Furthermore, detailed technical regulations under the Regulation of the Minister of ATR/BPN No. 3 of 2023 are essential. These regulations must address data classification, access authorization, and technical safeguards. Such measures will protect privacy, uphold transparency, and support the effective implementation of electronic land certificates in the digital era.